The Role of Land Registration in Spatial Planning: A Comparative Study of Indonesia and USA - Brian Mochamad Fahmi; Handar Subhandi Bakhtiar (Rechtenstudent, 2025)
The government holds the obligation to ensure legal certainty over land ownership, control, and utilization through a structured land registration system. The state bears the interest in regulating the relationship between land rights and spatial planning as the foundation for sustainable land use control. This research examines the relationship between the land registration system and spatial planning policies in the practice of land administration in Indonesia and the United States. This study also analyzes the effectiveness of the land registration system as an instrument to support the implementation of spatial planning. The method used in this research is normative juridical, based on legal literature, statutory regulations, and comparative law approaches. The results show that the land registration system in Indonesia remains declarative and has not been substantially integrated with the spatial planning system. The Indonesian government has not yet established a technical mechanism to functionally align land data with spatial plans. The United States government has developed institutional integration between land registration and zoning regulations. The legal system in the United States demonstrates a higher degree of effectiveness in using land registration as a tool to control land use. The Indonesian government needs to strengthen its legal and institutional framework to enable land registration to function as a legal instrument for efficient and sustainable spatial planning.